Цифровое ГТО - Грамотность. Технологии. Образование: электронный курс - Ситникова О. В. Оксана Валерьевна; Лобаненко О. Б. Ольга Борисовна; Исаева Е. В. Евгения Владимировна; Решетникова С. Л. Светлана Леонидовна; Ряшенцев И. В. Игорь Владимирович (Томск, TPU Moodle, 2020)
Заглавие с экрана